Assessment of the antibacterial, cytotoxic and antioxidant activities of Morus nigra L. (Moraceae) - G. R. Souza; R. G. Oliveira-Junior; T. C. Diniz; A. Branco; S. R. G. Lima-Saraiva; A. L. Guimarães; A. P. Oliveira; A. G. M. Pacheco; M. G. Silva; M. O. Moraes-Filho; M. P. Costa; C. Ó. Pessoa; et al. (Brazilian Journal of Biology, 2017)
Abstract This study was carried out to assess the antibacterial, cytotoxic and antioxidant activities of extracts of Morus nigra L. HPLC was used to determine the fingerprint chromatogram of the crude ethanolic extract (Mn-EtOH). The antibacterial effect was assessed through the method of microdilution. The cytotoxicity was tested against human tumour cell lines using the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. The total phenolic and flavonoid contents were also assessed through the Folin-Ciocalteu and aluminum chloride methods, respectively. Antioxidant activities of the extracts were evaluated by using 2,2-diphenyl-1-picrylhydrazil (DPPH) radical scavenging and β-carotene-linoleic acid bleaching methods. The presence of phenolic compounds in Mn-EtOH was confirmed using HPLC. The extracts showed activity against most microorganisms tested. The extracts did not show any expressive antiproliferative effect in the assessment of cytotoxicity. The most significant total phenolic content was 153.00 ± 11.34 mg of gallic acid equivalent/g to the ethyl acetate extract (AcOEt). The total flavonoid content was 292.50 ± 70.34 mg of catechin equivalent/g to the AcOEt extract, which presented the best antioxidant activity (IC50 50.40 ± 1.16 μg/mL) for DPPH scavenging. We can conclude that this species shows strong antibacterial and antioxidant activities, as well as weak cytotoxic effects.